2021
DOI: 10.3897/arphapreprints.e70930
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geographical and temporal distribution of hawkmoth (Lepidoptera: Sphingidae) species in Africa

Abstract: Hawkmoths consist of both diurnal and nocturnal species that are an important component of tropical ecosystems, with significant roles as major pollinators of both crops and wild flora. Pollinators are in decline world-wide and there is need for baseline data to inform their conservation strategies. Species data from Museum collections have been shown to be of great value as a tool for prioritising conservation actions in Africa. The National Museums of Kenya (NMK) has a large active entomology collection that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…This study reported that the majority (77%) of the respondents use condoms during sexual intercourse with their clients. This finding is like that in Majenro, Kenya, by [15] which reported 77% but higher than 63% consistent condom use among FSWs reported in Nairobi Kenya [16]. However, a higher proportion (90.2%) using a condom during sexual intercourse was reported in a Madagascar study [17].…”
Section: Discussionsupporting
confidence: 78%
“…This study reported that the majority (77%) of the respondents use condoms during sexual intercourse with their clients. This finding is like that in Majenro, Kenya, by [15] which reported 77% but higher than 63% consistent condom use among FSWs reported in Nairobi Kenya [16]. However, a higher proportion (90.2%) using a condom during sexual intercourse was reported in a Madagascar study [17].…”
Section: Discussionsupporting
confidence: 78%